THE EFFECT OF MADRASAH RESIDENTS' BEHAVIOR IN INCREASING SCHOOL COMPETITIVENESS - Fathur Rochim; Sevia Umi Wardini; Fakhruddin Al Farisy; Rona Merita (AL-MAFAZI: JURNAL MANAJEMEN PENDIDIKAN ISLAM, 2024)
Madrasah culture is indeed a barometer of Madrasah activities which is a measure of whether the Madrasah has a culture that produces good results for the Madrasah or vice versa a bad culture for the Madrasah, therefore MAN 1 and 4 Jombang really prioritize Madrasah Culture in increasing the competitiveness of their institutions so that the institution has an icon and good habits in everyday life at the Madrasah so as to increase the competitiveness of the Madrasah. This study aims to describeFinding and analyzing the behavior of Madrasah residents in increasing competitiveness at MAN 1 Jombang and MAN 4 Jombang and This study uses a qualitative approach with a multi-site study design. The reason the researcher chose MAN 1 Jombang and MAN 4 Jombang is because they have similarities in terms of madrasah culture in increasing competitiveness, therefore the researcher chose both institutions to be the object of research. Data collection in this study used in-depth interview techniques, observation, and documentation where the data sources were from people , documents ( paper ) and places ( place ). While the key informants in this study consisted of: the Head of Madrasah, the Deputy Curriculum and stakeholders of MAN 1 Jombang and MAN 4 Jombang who were involved. As for behavior residents of MAN 1 Jombang and MAN 4 Jombang, namely: a). Declaring madrasah activities that make madrasah residents comfortable and safe. b). Upholding the values of Islamic boarding schools in the madrasah. c). In the daily activities of madrasah residents, it has been regulated according to the madrasah culture program. d). Providing duties and functions in the behavior of madrasah residents so as to increase the competitiveness of the madrasah. e). Creating a comfortable atmosphere for madrasahs that have many madrasah activities, both intra and extra. f). Providing periodic counseling every time there will be and during activities. g). Madrasah cultural behavior is very dependent on the quality culture in both locations because the quality culture provides a rhythm of good habits in increasing the competitiveness of the madrasah. h). and also the last finding of the research on the behavior of madrasah residents is the existence of a culture of achievement and a regular bureaucratic culture from both locations, so that the behavior of madrasah residents is created with achievement and regular discipline in increasing the competitiveness of the madrasah. Keywords: Effectiveness, Madrasah Community Behavior, Competitiveness